The Effect Of Health Education On Improving Parents 'Knowledge About Diarrhea Management In Children - Nadia Alfira; Fatmawati; Nurhasanah (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2019)
Diarrhea is almost one in five child deaths caused by diarrhea in developing countries. Based on data obtained from the medical records of Sinjai Regional Hospital in 2016 the number of diarrhea patients in children was 195 cases (43%), in 2017 there were 117 cases (26%), and in 2018 the number of diarrhea patients was 136 cases (30%). One of the causes of the increasing incidence of diarrhea is the low level of parental knowledge about diarrhea management, so it is necessary to increase the knowledge of parents in diarrhea management. This study aims to determine the